Topiramate Add-on Lithium Carbonate for Treatment of Acute Mania - Mirsepassi, Zahra (Mazandaran University of Medical Sciences, 2013)
Objective: The purpose of this study was to evaluate the effect of adjunctive topiramate in treating acute mania. Methods: In this study which was a double-blinded randomized clinical trial, 46 bipolar patients in manic episode, were treated with lithium carbonate and topiramate versus lithium carbonate and placebo and treatment responses were assessed by Young Mania Rating Scale (YMRS) weekly. Results: In both intervention and control groups, YMRS score had significant decline after 8 weeks(p < 0.001), but there was no statistically significant difference between the two groups (p = 0.419). The highest score decline was after two weeks. YMRS score at baseline did not have statistically significant difference between the intervention and control groups (p = 0.709). Conclusions: This study failed to show antimanic efficacy of adjunctive topiramate in the treatment of those with acute manic. Declaration of interest: None. Clinical Trial Registration: URL: http://www.irct.ir.IRCT201110317960N1.